The bactericidal potential of LLDPE with TiO2/ZnO nanocomposites against multidrug resistant pathogens associated with hospital acquired infections. Issue 14 (21st September 2020) - Harun, Nor Hazliana; Mydin, Rabiatul Basria S. M. N; Sreekantan, Srimala; Saharudin, Khairul Arifah; Basiron, Norfatehah; Seeni, Azman
Abstract: The emerging polymer nanocomposites have received industrial interests in diverse fields because of their added value in metal oxide-based nanocomposites, such as titanium (TiO2 ) and zinc oxide (ZnO). Linear low-density polyethylene (LLDPE)-based polymer has recently generated a huge market in the healthcare industry. TiO2 and ZnO are well known for their instant photocatalytic killing of hospital-acquired infections, especially multidrug-resistant (MDR) pathogens. This study investigated the actions of LLDPE/TiO2 /ZnO (1:3) nanocomposites in different weight% against two representative MDR pathogens, namely, methicillin-resistant Staphylococcus aureus (MRSA) and Klebsiella pneumonia ( K.pneumoniae ). Antibacterial activities were quantified according to international standard guidelines of CLSI MO2-A11 (static condition) and ASTM E-2149 (dynamic condition). Preliminary observation via a scanning electron microscope revealed that LLDPE matrix with TiO2 /ZnO nanocomposites changed the bacterial morphology and reduced the bacterial adherence and biofilm formation. Furthermore, a high ZnO weight ratio killed both types of pathogens. The bactericidal potential of the nanocomposite is highlighted by the enhancements in photocatalytic activity, zinc ion release and reactive species, and bacteriostatic/bactericidal activity against bacterial growth. This study provides new insights into the MDR-bactericidal potential of LLDPE with TiO2 /ZnO nanocomposites for targeted healthcare applications.